2001
DOI: 10.1523/jneurosci.21-17-06522.2001
|View full text |Cite
|
Sign up to set email alerts
|

ATP P2X Receptor-Mediated Enhancement of Glutamate Release and Evoked EPSCs in Dorsal Horn Neurons of the Rat Spinal Cord

Abstract: Presynaptic ATP P2X receptors have been proposed to play a role in modulating glutamate release from the first sensory synapse in the spinal cord. Using spinal cord slice preparations and patch-clamp recordings from dorsal horn neurons in lamina V of the rat spinal cord, we showed that the activation of P2X receptors by ␣,␤-methylene-ATP (␣␤m-ATP) resulted in a large increase in the frequency of spontaneous EPSCs (sEPSCs) and miniature EPSCs (mEPSCs). The increases in mEPSC frequency by ␣␤m-ATP were not blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
127
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 43 publications
16
127
1
Order By: Relevance
“…As the present and other studies have shown, the primary afferent neurons express both P2X 2 and P2X 3 receptors. In vitro studies in the spinal dorsal horn have show that the P2X receptor agonist α ,β-meATP causes an increase in glutamatergic (Nakatsuka and Gu, 2001;Nakatsuka et al, 2002;Nakatsuka et al, 2003;Tsuzuki et al, 2003). We have reported analogous results in the medullary dorsal horn (Jennings et al, 2006).…”
Section: Functional Roles Of P2x Receptors In Nociceptive Signallingsupporting
confidence: 71%
See 1 more Smart Citation
“…As the present and other studies have shown, the primary afferent neurons express both P2X 2 and P2X 3 receptors. In vitro studies in the spinal dorsal horn have show that the P2X receptor agonist α ,β-meATP causes an increase in glutamatergic (Nakatsuka and Gu, 2001;Nakatsuka et al, 2002;Nakatsuka et al, 2003;Tsuzuki et al, 2003). We have reported analogous results in the medullary dorsal horn (Jennings et al, 2006).…”
Section: Functional Roles Of P2x Receptors In Nociceptive Signallingsupporting
confidence: 71%
“…In the spinal somatosensory system, all P2X receptor subtypes with the exception of P2X 7 are expressed in the spinal dorsal horn, the dorsal root ganglion (DRG), and the central terminals of primary afferent neurons (Burnstock, 2000;Khakh, 2001;North, 2002). In vivo and in vitro electrophysiological recordings from single dorsal horn neurons have implicated P2X receptors on primary afferent terminals in spinal nociceptive transmission (Nakatsuka and Gu, 2001;Nakatsuka et al, 2002;Nakatsuka et al, 2003; Correspondence details: Dr. Ernest Jennings Dept. Anatomy & Cell Biology The University of Melbourne Parkville, Victoria, 3010, Australia Tel: +61 3 8344 5802 Fax: +61 3 9347 9619 Email: e.jennings@unimelb.edu.au.…”
mentioning
confidence: 99%
“…Previous studies suggest that P2X receptors modulate glutamatergic and GABAergic synaptic transmission in the CNS, namely spinal cord, the nucleus tractus solitarius, medial habenula, locus coeruleus, hippocampus, and somatosensory cortex (Bardoni et al, 1997;Evans et al, 1992;Gu and MacDermott, 1997;Hugel and Schlichter, 2000;Jin et al, 2004;Mori et al, 2001;Nakatsuka and Gu, 2001;Nieber et al, 1997;Pankratov et al, 1998). For example, activation of P2X receptors has been shown to presynaptically alter the release of glutamate, GABA, glycine and vasopressin (Jin et al, 2004;Khakh and Henderson, 2000;Nakatsuka and Gu, 2001;Rhee et al, 2000;Troadec et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although a slight potentiation of the sEPSC amplitude (a measure of postsynaptic sensitivity) occurred in some of the experiments, the facilitation of the sEPSC frequency (a measure of spontaneous transmitter release) was a much more pronounced phenomenon. The enhancement of spontaneous glutamatergic transmission by ATP has been reported originally for the nociceptive afferent pathways to lamina V [22] and I [23] in the spinal cord dorsal horn. In this case, the general P2 receptor agonist ATP and the P2X1,3 selective agonist α,β-meATP had comparable activities, indicating the involvement of pain-relevant, presynaptic P2X3 receptors [24].…”
Section: Discussionmentioning
confidence: 67%